Treatment with rapamycin or rapamycin in combination with metformin contributes to mechanisms of mitochondrial proteostasis in vivo and in vitro - Wolff, Christopher Andrew, author; Hamilton, Karyn L., advisor; Miller, Benjamin F., advisor; Hickey, Matthew, committee member; Pagliassotti, Michael, committee member (Colorado State University. Libraries, 2018)
This dissertation describes three sets of experiments with an overall objective of understanding how lifespan-extending treatments influence mechanisms of mitochondrial protein homeostasis (proteostasis). The specific aims of the three experiments were to 1) determine how the mTORC1 inhibitor rapamycin (Rap), or the anti-diabetes medication metformin in combination with rapamycin (Met+Rap) influence mitochondrial protein synthesis in young mice, and to determine if there are sex-specific differences in protein synthesis following treatment with Rap or Met+Rap; 2) examine the influence of Met+Rap treatment on protein synthesis in the heart, liver, and skeletal muscle of older mice and to determine if there are sex-specific differences in protein synthesis following Met+Rap treatment in old mice; 3) and, finally, to investigate the regulation of how protein turnover contributes to maintaining proteostasis during Rap and Met+Rap treatment, and the contribution of autophagic and mitophagic flux to protein turnover in cultured skeletal myotubes. In the first experiment, both Rap and Met+Rap treatments lowered mitochondrial protein synthesis in male mice compared to control in skeletal muscle. However, in female mice, only Met+Rap treatment significantly lowered skeletal muscle mitochondrial protein synthesis compared to control. Additionally, both Rap and Met+Rap treatments significantly elevated skeletal muscle mitochondrial protein synthesis in female animals compared to males. However, in the heart and liver tissue, there were no differences in mitochondrial protein synthesis between treatments or sexes. In the second experiment, Met+Rap treatment lowered protein synthesis in all three tissues, but in a fraction-specific manner. independent of sex-differences in old mice. For the third experiment, we measured protein synthesis and protein breakdown in cultured skeletal myotubes treated with Rap and Met+Rap. Rap treatment significantly increased mitochondrial protein:DNA compared to control, while Met+Rap did not. We demonstrate that autophagic flux is a large (29%) contributing process to degradation of mitochondrial proteins. Additionally, mitochondrial fission is not essential for mitochondrial protein degradation. The data from these experiments demonstrate that despite sexually dimorphic effects on lifespan, Rap and Met+Rap treatments both enhance the contribution of protein synthesis to maintaining proteostasis in vivo. Further, we demonstrate that both Rap and Met+Rap treatment increased protein:DNA in cultured skeletal myotubes. In summary, these data demonstrate that Rap and Met+Rap treatments increase proteostatic mechanisms, and further research is required to improve the understanding of how Met+Rap treatment influences lifespan.